2017
DOI: 10.1038/jes.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal occupational exposures and hepatoblastoma: results from the HOPE study through the Children’s Oncology Group

Abstract: Introduction Little is known about the etiology of hepatoblastoma. We aimed to confirm the results of a previous study evaluating the association between parental occupational exposures and hepatoblastoma. Methods In our case-control study, we identified cases (n=383) from the Children’s Oncology Group and controls from birth certificates (n=387), which were frequency matched to cases on year and region of birth, sex, and birth weight. Occupational exposure in the year prior to and during the index pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The social factor (race) is an independent prognostic factor for HB. Similar findings were also noted in a previous study conducted in the USA ( 11 ). Black patients tend to have poor outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…The social factor (race) is an independent prognostic factor for HB. Similar findings were also noted in a previous study conducted in the USA ( 11 ). Black patients tend to have poor outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon is partly due to increased prematurity Ivyspring International Publisher and very low birth weight [4,5]. The development of hepatoblastoma is also associated with some environmental factors, such as parental exposure to tobacco, metal and petroleum products [6][7][8][9]. Moreover, it is strongly associated with familial adenomatous polyposis [10], Beckwith-Wiedemann syndrome [11], and Glycogen storage disease [12], indicating some genetic underpinnings.…”
Section: Introductionmentioning
confidence: 99%
“…Janitz et al. had confirmed that maternal and paternal occupational exposures to paints were etiologically relevant to hepatoblastoma ( 44 ). Other studies indicated that parental occupational exposures to wood dust, metal fumes, and petroleum products also could be the risk factors ( 45 , 46 ).…”
Section: Risk Factorsmentioning
confidence: 99%